Morphological Characteristics of Quality Levels How To Make Level Forms - Ochilova Nigora Normurodovna (Academia One Publishing, 2024)
In this article, linguists expressed their valuable opinions about the functional basis of grammar. These scientists based the idea of logical-thinking categories and interpreted these categories as categories that are formed in the harmony of logical and grammatical phenomena.
Keywords: functional-semantic; grammatical content; lexical units